Peran Ombudsman dalam Mendukung Tercapainya Tujuan Pembangunan Berkelanjutan Melalui Good Governance - Sariati, Muhamad Ali (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This paper analyzes the role of the Ombudsman as an independent state institution in supervising the implementation of public services in Indonesia. The Ombudsman was established to accommodate the dynamics of society and ensure good governance. With seven main characteristics of an independent state institution, the Ombudsman has the authority to supervise maladministration of public service providers. This study shows that the Ombudsman carries out an important external oversight function in the Indonesian government system. The Ombudsman's supervision is repressive, namely responding to public complaints regarding violations in the implementation of public services. Nevertheless, the existence of the Ombudsman is an important mechanism in ensuring that state administrators are accountable for their actions and provide quality public services. Looking at the role of the Ombudsman in supporting the achievement of the Sustainable Development Goals (SDGs) through the lens of good governance. The importance of the Ombudsman's role in supervising the implementation of public policies that have an impact on the achievement of the SDGs. In addition, it also provides policy recommendations to strengthen the role of the Ombudsman in supporting the realization of sustainable development, including strengthening institutions, increasing coordination, and socialization to the community.